Water-Solubilization of P(V) and Sb(V) Porphyrins and Their Photobiological Application - Jin Matsumoto; Tsutomu Shiragami; Kazutaka Hirakawa; Masahide Yasuda (International Journal of Photoenergy)
Porphyrins have been widely utilized as biochemical and biological functional chromophores which can operate under visible-light irradiation. Water-soluble porphyrins have been used as the drug for photodynamic therapy (PDT) and photodynamic inactivation (PDI). Although usual water-solubilization of porphyrins has been achieved by an introduction of an ionic group such as ammonium, pyridinium, sulfonate, phosphonium, or carboxyl to porphyrin ring, we proposed the preparation of water-soluble P and Sb porphyrins by modification of axial ligands. Alkyl (type A), ethylenedioxy (type E), pyridinium (type P), and glucosyl groups (type G) were introduced to axial ligands of Sb and P porphyrins to achieve water-solubilization of Sb porphyrin and P porphyrins. Here, we review their water-soluble P and Sb porphyrins from the standpoints of preparation, bioaffinity, and photosensitized inactivation.